Ответ:
Пошаговое объяснение:47) 5(2x-1)=8x+1
10x-5=8x+1
10x-8x=1+5
2x=6
X=3
48) (y+4)-(y-1)=6y
Y+4-y+1=6y
Y-y-6y=-4-1
-6y=-5
Y=-5/-6
Y=5/6
49) 3p-1-(p+3)=1
3p-1-p-3=1
3p-p=1+1+3
2p=5
P=5÷2
P=2,5
1)(127+89)*305-42993=3404422
2) 59057/73+239*49=12,520
3)139725/405-151892/508=46
4)7410+51642/(517+389)=7467
5)81*(2423-1879)/36=1224
6)(10034-17514/21)*25=230000
46. 1)7*65+7*35+3*35+3*55=970
2)8*3+3*93+8*97+3*7=1100
3)37*49+37*51+63*49+51*63=10000
4)819*73+181*27+73*181+27*819=100000
89см< 1м
100см=10дм
27мм<20см
145см<1м55см